Assessing Iranian Elementary Language Arts Textbooks from a Critical Literacy Perspectives - Tayebeh Sohrabi (Canadian Society for Studies in Education, 2022)
This study investigated Iranian elementary language arts textbooks from a critical literacy perspective. A content analysis methodology was adopted to examine how and to what extent critical literacy is developed in Iranian elementary language arts textbooks. The content included words, pictures, and questions of all Iranian elementary language arts textbooks from grades one to six. In Iran, the same textbooks are taught at schools across the country. This study's criteria were developed according to the criteria identified by Klenner and Sandretto (2011) and Belet and Dala (2010). Analysis of the data followed Ball and Smith's (1992) content analysis phases. The analysis revealed that even though the Iranian textbooks meet the criteria, they do not seem to fully cover the essence of critical literacy. There might be several reasons for this, such as ignorance, unequal power relationships, and the profit of authorities.